Exploring Work and Energy Concept with Indonesian Traditional Game "Egrang": An Ethno-pedagogical Approach to Physics Learning - Wulandari, Riska; Fatmaryanti, Siska Desy (Journal of Science and Science Education, 2024)
Egrang are a traditional Indonesian game that can be used as a learning medium. This research aims to analyze the physical concepts of work and energy in the traditional game "Egrang" through an ethno-pedagogical approach. This research was conducted with a descriptive review. The learning analysis stage uses a literature review by reviewing several journals to be analyzed in accordance with existing physics concepts, namely the concept of work and energy and ethno-pedagogical approach analysis. The research results found that the concepts of work, kinetic energy, potential energy and mechanical energy can be explained using stilts. And in implementing learning, you can use 5 learning steps with an ethno-pedagogical approach. It is hoped that these results can serve as an initial study at the implementation stage in schools to prove the effectiveness of learning